Spiradenocarcinoma arising from a spiradenocylindroma: unusual case with lymphoepithelioma-like areas. - Chetty, R; Perez-Ordonez, B; Gilbert, R; Pagedar, N; Waldron, J; Ghazarian, D (2009)
BACKGROUND: Hybrid skin adnexal tumors are common, and spiradenocylindroma is well described. OBJECTIVE: However, malignant transformation in this setting is infrequent, especially resemblance to lymphoepithelioma-like carcinoma of skin, which is not associated with Epstein-Barr virus. METHODS: A 65-year-old female presented with ataxia and a skin nodule composed of a hybrid adnexal tumor (spiradenoma and cylindroma) that transitioned into an undifferentiated carcinoma with attendant lymphocytes and plasma cells. There was widespread dissemination of the undifferentiated component to regional neck lymph nodes. RESULTS: The undifferentiated component resembled a lymphoepithelioma-like carcinoma and showed focal evidence of tubular and squamous differentiation. The tumor was Epstein-Barr encoded RNAs (EBER) negative by in situ hybridization. No evidence of neuroendocrine differentiation was seen in the tumor, despite the patient having symptoms of paraneoplastic ataxia that improved after surgery. CONCLUSION: This case highlights the transition of a benign hybrid tumor (spiradenocylindroma) into a spiradenocarcinoma that resembled lymphoepithelioma-like carcinoma of skin. It also highlights two unusual features: widespread lymph node dissemination and presentation with paraneoplastic syndrome-associated ataxia.